(untitled) (Research, Society and Development, 2021)
The dissemination and sharing of knowledge produced by postgraduate courses in Brazil are part of a public policy, with the purpose of stimulating innovation and, consequently, the competitiveness of the Brazilian productive sector. The present research is a literature review study, with the objective of epistemologically understanding the role of postgraduate courses in the Brazilian social scenario, thus outlining the best way to establish a management aimed at meeting its purposes. The study has a qualitative and explanatory approach. The method adopted by the research was the literature review, having met the inclusion and exclusion criteria of the sample, 17 studies published after 2004 were included in the study sample, under the validity of the innovation law, which were analyzed in an explanatory manner. The conclusion of the study goes back to the understanding that postgraduate programs must act strategically, always observing market demands and making their productions to meet them, generating circulation of wealth and strengthening the production of innovative products in Brazilian society, inserting Brazil in the international commercial scene.